A FISIOTERAPIA NA SALA DE RECUPERAÇÃO PÓS-ANESTÉSICA: UMA ATUAÇÃO NECESSÁRIA - Coracini, Maria A.; Marchi, Genara J. D.; Klahr, Patrícia d. S.; Windmöller, Pollyana; Souza, Regina M. H. d.; Reis, Lenara d. C.; Sfalcin, Janaina L.; Andrade, Fernanda P. d.; Lorenzoni, Juliara W.; Mergen, Carla T. T.; Pasqualoto, Adriane S. (Salão do Conhecimento, 2013)
Resumo